A study on attitude of students towards statistics in UiTM Kedah / Ida Normaya Mohd Nasir, Wan Zulkipli Wan Salleh and Wan Siti Esah Che Hussain - Mohd Nasir, Ida Normaya; Wan Salleh, Wan Zulkipli; Che Hussain, Wan Siti Esah (Research Management Institute (RMI), 2012)
Malaysia aspires to be a fully developed country by the year 2020. This has been outlined in what is known as Vision 2020. The sixth challenge is that of establishing a scientific and progressive society that is not only a consumer in technology but also a contributor to scientific and technological civilisation of the future. Universiti Teknologi MARA (UiTM) has recognised that the university has to be restructured in order to face new challenges in this era of globalisation and ICT propagation. Under UiTM's restructuring programmes, the university aims to increase the number of full-time students enrolled in science and technology courses to 60% of all students by the year 2015 (UiTM 2004).